Multiscale integrated analysis of societal and ecosystem metabolism of Qatar - Abdulrahman Al-Tamimi; Sami G. Al-Ghamdi (Energy Reports, 2020)
Energy consumption per capita in Qatar reached 17,418~kg of oil equivalent in 2014 which make Qatar one of the biggest energy consumers around the world. Therefore, the Multiscale Integrated Analysis of Societal and Ecosystem Metabolism (MuSIASEM) approach has been employed to analyze energy metabolic pattern of socio-economic dimensions of Qatar for the period between 2006 and 2015. The results investigate the relationship between GDP, economic activities, energy consumption, and human time, to determine energy intensity, exosmotic metabolic rate, and economic labor productivity. The major findings show that energy consumption grew at a faster rate than GDP within the same period, and energy consumption per capita and energy intensity grew approximately at the same rate. Besides, the low rate of labor productivity in construction sector drags down the economic labor productivity for the entire economy, especially with the large number of labor in construction sector. Moreover, the correlation between exosomatic metabolic rate and economic labor productivity in the manufacturing sector is unbalanced, whereas the high rates of energy consumption per hour do not depict the low rates of economic labor productivity. Relevant policy decisions can then be formulated and implemented based on the recommendations of this study to help policy makers in the implementation of Qatar National Vision 2030.
Keywords: 330; Economic labor productivity; Energy intensity; Energy metabolism; Exosomatic metabolic rate; MuSIASEM